2012
DOI: 10.1029/2012tc003138
|View full text |Cite
|
Sign up to set email alerts
|

The 2005 volcano‐tectonic earthquake swarm in the Andaman Sea: Triggered by the 2004 great Sumatra‐Andaman earthquake

Abstract: A 6 day duration earthquakes swarm occurred in the Andaman Sea, 31 days after the giant 2004 Sumatra‐Andaman earthquake (Mw 9.2). The swarm occurred less than 100 km from the eastern edge of the 2004 earthquake rupture and is the most energetic ever recorded in the world. The earthquakes swarm appear to have occurred on en echelon fault system bounded by the two main right‐lateral strike‐slip faults, namely, the Seulimeum Strand of Sumatra Fault system (SEU) and the West Andaman Fault (WAF). At the beginning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…On the other hand, Kundu et al . [] and Kamesh Raju et al . [] suggest that the volcanism and strike‐slip faults are linked, and the 2005 swarm was due to stress induced by the 2004 earthquake.…”
Section: Seismic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Kundu et al . [] and Kamesh Raju et al . [] suggest that the volcanism and strike‐slip faults are linked, and the 2005 swarm was due to stress induced by the 2004 earthquake.…”
Section: Seismic Resultsmentioning
confidence: 99%
“…The volcanic melt seems to have been produced by melting at depth (60-80 km) and passed through the mantle and crust without affecting the rheology, and therefore, the volcanoes must be very superficial features along the volcanic arc. On the other hand, Kundu et al [2012] and Kamesh Raju et al [2012] suggest that the volcanism and strike-slip faults are linked, and the 2005 swarm was due to stress induced by the 2004 earthquake.…”
Section: Profile Pgs08-06mentioning
confidence: 99%
“…This WNW-ESE extension direction, perpendicular to the convergence vector (Figure 12A), is suggested by the collected structural field data in the central and southern part of the GSF (Figures 9, 10) and is also supported by structural and geophysical studies (Lassal et al, 1989;Harjono et al, 1991;Pramumijoyo and Sébrier, 1991;Mount and Suppe, 1992;Kundu et al, 2012;Muksin et al, 2014). The ∼WNW-ESE extension direction may explain the common ∼NNE-SSW elongation and/or alignment of many volcanoes (Figure 8).…”
Section: Discussionmentioning
confidence: 55%
“…The 2004 mega-earthquake was followed, 1 month later, by a seismic swarm in the Andaman Sea north of Sumatra (Kundu et al, 2012) and volcanism, as testified by a submarine eruption . In particular, this seismicity is at first consistent with the regional tectonic setting and, subsequently, with the involvement of fluids, also magmatic, producing normal faults along a NNE-SSW direction (Kundu et al, 2012).…”
Section: Tectonic Setting Of Sumatramentioning
confidence: 99%
“…Kamesh Raju et al () showed that the swarm localized on a dormant seamount and documented evidence for former hydrothermal activity and manganese nodules. Mukhopadhyay and Dasgupta () and Mukhopadhyay et al () argued that the swarm demonstrated a complex faulting series with “initially ... strike‐slip motion followed by normal faulting in repetitive sequences, whose representative fault planes orient at high angle to the regional faults.” These authors suggest a nascent rift segment forming in a ~NW‐SE trending direction and discuss a “pressure front from ascending magmatic fluid.” Kundu et al () continue this discussion.…”
Section: Decomposition Of a Complex Scatterplotmentioning
confidence: 99%